Hepatitis E virus infection is highly prevalent among pregnant women in Accra, Ghana - Adjei, A.A.; Tettey, Y.; Aviyase, J.T.; Adu-Gyamfi, C.; Obed, S.; Mingle, J.A.; Ayeh-Kumi, P.F.; Adiku, T.K. (My University, 2009)
Abstract Background Hepatitis E virus (HEV) is highly endemic in several African countries with high mortality rate among pregnant women. The prevalence of antibodies to HEV in Ghana is not known. Therefore we evaluated the prevalence of anti-HEV IgG and anti-HEV IgM among pregnant women seen between the months of January and May, 2008 at the Obstetrics and Gynaecology Department, Korle-Bu Teaching Hospital, Accra, Ghana. Results One hundred and fifty-seven women provided blood samples for unlinked anonymous testing for the presence of antibodies to HEV. The median age of participants was 28.89 ± 5.76 years (range 13–42 years). Of the 157 women tested, HEV seroprevelance was 28.66% (45/157). Among the seropositive women, 64.40% (29/45) tested positive for anti-HEV IgM while 35.60% (16/45) tested positive to HEV IgG antibodies. HEV seroprevalence was highest (46.15%) among women 21–25 years of age, followed by 42.82% in = 20 year group, then 36.84% in = 36 year group. Of the 157 women, 75.79% and 22.92% were in their third and second trimesters of pregnancy, respectively. Anti-HEV antibodies detected in women in their third trimester of pregnancy (30.25%) was significantly higher, P < 0.05, than in women in their second trimester of pregnancy (25.0%). Conclusion Consistent with similar studies worldwide, the results of our studies revealed a high prevalence of HEV infection in pregnant women.